Antibiotic usage in surgical prophylaxis: a prospective observational study in the surgical wards of a tertiary care hospital - Vijayarani, G.; T., Blessina Paulin; Sudha, K.; Vadivoo, N. Shanmuga; Sasikala, G.; Usha, B. (International Journal of Research in Medical Sciences, 2025)
Background: Surgical site infections (SSIs) are a leading cause of postoperative complications, particularly in resource-limited settings. Surgical antibiotic prophylaxis (SAP) is an effective measure for preventing SSIs when administered with appropriate antibiotic selection, timing, and duration. This study aimed to evaluate the SAP practices in elective surgeries and assess adherence to national and international guidelines. Methods: A prospective observational study was conducted over six months at a tertiary care teaching hospital, including 293 patients undergoing elective surgical procedures in the departments of general surgery, orthopaedics, ENT, gynaecology, and obstetrics. Data on the choice of prophylactic antibiotics, timing relative to surgical incision, and duration of postoperative use were collected and compared with guidelines from the Indian council of medical research (ICMR), American society of health-system pharmacists (ASHP), and the world health organization (WHO). Results: General surgery accounted for 51.9% of procedures, followed by orthopaedics (25%) and ENT (13.5%), with gynaecology and obstetrics together at 9.6%. Cefotaxime was the most frequently used antibiotic, particularly in obstetrics (100%) and general surgery (70.4%), whereas gynaecology predominantly used a cefotaxime-metronidazole combination (66.7%). SAP was administered within the recommended 60-minute window before incision in 80.7% of cases, with the highest adherence in obstetrics (100%). Discontinuation within 24 hours occurred in 77.8% of general surgery and 92.3% of orthopaedic cases, whereas extended use was common in obstetrics, ENT and gynaecology. Conclusions: Although SAP timing was generally appropriate, the overuse of third-generation cephalosporin, the absence of cefazolin, and prolonged prophylaxis in some departments highlight the need for department-specific guideline adherence.